Strong-field dissociation dynamics of molecular dications. (August 2015) - Jochim, Bethany; Severt, T; Zohrabi, M; Ablikim, U; Berry, Ben; Gaire, B; Betsch, K J; Anis, F; Uhlíková, Tereza; Carnes, K D; Wells, E; Esry, B D; et al.
Synopsis: We focus on the dissociation of metastable molecular dications induced by intense, ultrafast laser pulses. In particular, we demonstrate the dominant role of commonly-neglected permanent-dipole transitions and drive dissociation via a pump-dump-like mechanism within a single laser pulse.